2015
DOI: 10.1016/j.jbiotec.2015.06.427
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of CRISPR–Cas9 mismatch tolerance reveals low levels of off-target activity

Abstract: The discovery that the bacterial clustered regularly interspaced short palindromic repeats (CRISPR)-CRISPR-associated protein 9 (Cas9) acquired immune system can be utilized to create double-strand breaks (DSBs) in eukaryotic genomes has resulted in the ability to create genomic changes more easily than with other genome engineering techniques. While there is significant potential for the CRISPR-Cas9 system to advance basic and applied research, several unknowns remain, including the specificity of the RNA-dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
105
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(122 citation statements)
references
References 38 publications
10
105
0
Order By: Relevance
“…Since these alleles should carry similar fitness costs as the driver, they are not likely to rise in frequency. However, resistance may still evolve if some mutations change the target sequence without actually disrupting the gene, or if the ability to drive itself is already associated with some fitness costs, as will likely be the case if off-target effects of the driver have not been completely suppressed (Fu et al 2013;Anderson et al 2015;Zhang et al 2015). Another proposed strategy is the insertion of a new gene (e.g., a gene that prevents mosquitoes from transmitting malaria).…”
Section: Discussionmentioning
confidence: 99%
“…Since these alleles should carry similar fitness costs as the driver, they are not likely to rise in frequency. However, resistance may still evolve if some mutations change the target sequence without actually disrupting the gene, or if the ability to drive itself is already associated with some fitness costs, as will likely be the case if off-target effects of the driver have not been completely suppressed (Fu et al 2013;Anderson et al 2015;Zhang et al 2015). Another proposed strategy is the insertion of a new gene (e.g., a gene that prevents mosquitoes from transmitting malaria).…”
Section: Discussionmentioning
confidence: 99%
“…3a). When performing this analysis, it is important to remember that Cas9 can potentially also cut genes with a one base mismatch in the sequence, in particular if the mismatch is far from the PAM sequence, while for two mismatches the enzyme does not cut in approximately 96% of the cases24.…”
Section: Resultsmentioning
confidence: 99%
“…A recent report by Anderson et al . showed that 96% of the crRNAs with two mismatches were not functional24. For one mismatch the Cas9 can still work efficiently, in particular if the mismatch is far from the PAM-sequence.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major issues with CRISPR is the ability to ensure that only the target gene is edited and changes hazardous to the individual's health are not introduced throughout the genome. Unwanted off-target site mutations could invariably lead to further malignancies and undesirable phenotypes [25]. In a recent study by Huang et al researchers have demonstrated the ability to perform human embryo editing with CRISPR, potentially triggering ethical dilemmas across the community [26, 27].…”
Section: Concerns With the Technologymentioning
confidence: 99%